Validation of Innovative Behavior as A Multidimensional Construct - Amir, Muhammad Taufiq (Jurnal Manajemen Teknologi, 2015)
Abstract. Innovative behavior (IB) is imperative in ensuring organization innovation succeed but the measurement of IB is still at an evolutionary stage. Most literature treats IB as a single construct, ignoring its muldimensionality. Drawing from studies that indicating IB as a multidimensional, this study empirically examines and validates the dimensionality of IB construct and suggests a refined angle in seeing the process of individual innovation. Paper based and online survey completed by 211 employees from six industries in Indonesia and analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). Findings demonstrating initial supports that IB can be considered as a multidimensional, as three dimensions model shows a better fit model than two and single model. It may suggest IB dimensions can be seen overlapped each other, not only as different stages as commonly understood. Convergent and discriminant validity were evidenced, consistent with previous study. Managerial and theoretical implications in managing individual innovation, including the future research directions are also discussed.Keywords: Innovative behavior, multidimensional construct, convergent, divergent validity, structural equation modelingÂ Abstrak. Perilaku inovatif (PI) penting dalam memastikan kesuksesan inovasi organisasi namun pengukuran PI masih belum berkembang. Kebanyakan literatur menganggap PI sebagai konstruk tunggal, bukan sebagai multidimensional. Berdasarkan studi-studi yang mengindikasikah bahwa PI adalah multidimensi, studi ini secara empirik menganalisa dan memvalidasi dimensionalitas konstruk PI dan menyarankan perspektif baru dalam melihat proses inovasi individu. Survei dilakukan secara manual dan online pada 211 karyawan dari enam industry di Indonesia dan dianalisa dengan menggunakan confirmatory factor analysis (CFA) dan structural equation modelling (SEM). Temuan studi ini menunjukkan dukungan awal yang mendukung bahwa PI bisa dianggap sebagai konstruk multidimensi, karena model dengan tiga dimensi menunjukkan model fit yang lebih baik ketimbang model dengan dua dan satu dimensi. Ini menunjukkan bahwa dimensi IB bisa saja saling tumpang tindih, tidak hanya sebagai tahpaa yan berbeda seperti selama ini dipahami. Analisis validitas convergent dan discriminant yang dilakuan konsisten dengan studi-studi terdahulu. Implikasi manajerial dan teoretikal dalam mengelola inovasi individu, termasuk arah studi masa depan juga didiskusikan.Kata kunci: Perilaku inovatif, konstruk multi-dimensi, convergent, validitas divergen, structural equation modeling